Sagot :
(1.) First: (x . x) = x²
Outer: (x . -5) = (-5 . x) = -5x
Inner: (3 . x) = 3x
Last: (3 . -5) = -15
x²-5x+3x-15
= x²-5x+3x-15 --> -5x+3x = -2x
Final Answer = x² - 2x -15
(2.) First: (x . x) = x²
Outer: (x . 16) = (16 . x) = 16x
Inner: (-4 . x) = -4x
Last: (-4 . 16) = -64
x²+16x-4x-64
= x²+16x-4x-64 ---> 16x-4x = 12x
Final Answer: = x² + 12x - 64
(3.) First: (x . x) = x²
Outer: (x . -7) = (-7 . x) = -7x
Inner: (-20 . x) = -20x
Last: (-20 . -7) = 140
x²-7x-20x+140
= x²-7x-20x+140 = -7x-20x = -27x
Final Answer: = x² - 27x + 140
(4.) First: 7x²
Outer: 56x
inner: 9x
Last: 72
7x² + 56x + 9x + 72 = 56x + 9x = 65x
Final Answer: 7x² + 65x + 72
(5.) First: (5x . 2x) = 10x²
Outer: (5x . 11) = (11 . 5x) = 55x
Inner: (-1 . 2x) = -2x
Last: (-1 . 11) = -11
10x² + 55x - 2x - 11
= 10x² + 55x - 2x - 11 = (55x-2x = 53x)
Final Answer: 10x² + 53x - 11
(6.) First: x²
Outer: (x . 12) = (12 . x) = 12x
Inner: (5 . x) = 5x
Last: ( 5 . 12) = 60
x² + 12x + 5x + 60
Final Answer: x² + 17x + 60
